2009
DOI: 10.1007/s11172-009-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of μ-diborolyl triple-decker complexes [CpCo(1,3-C3B2Me5)Ru(arene)]+

Abstract: Cationic triple decker complexes [CpCo(1,3 C 3 B 2 Me 5 )Ru(arene)]PF 6 (arene is benzene (2a), p cymene (2b)) with a bridging diborolyl ligand were synthesized by the reaction of the sand wich anion [CpCo(1,3 C 3 B 2 Me 5 )] -(1) with [(arene)RuCl 2 ] 2 . The structure of [2b]PF 6 was confirmed by X ray diffraction analysis.The main method for the preparation of cationic triple decker complexes is the electrophilic stacking of sand wich compounds with the cationic fragments [(ring)M] n+ (n = 1, 2). 1-5 We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Structures of the triple-decker complexes 2a BPh 4 , 2b PF 6 , 4a PF 6 , 5a OTf, and 5c PF 6 were determined by X-ray diffraction (Figures –, respectively). Selected parameters for these structures and for the previously described 3b PF 6 , 4b PF 6 , and 5b PF 6 are given in Table (see also Table S1 in the Supporting Information for selected bond lengths and angles). All of the cations 2a , b , 3b , 4a , b , and 5a – c are formed by three cyclic ligands, between which two metal atoms are located.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures of the triple-decker complexes 2a BPh 4 , 2b PF 6 , 4a PF 6 , 5a OTf, and 5c PF 6 were determined by X-ray diffraction (Figures –, respectively). Selected parameters for these structures and for the previously described 3b PF 6 , 4b PF 6 , and 5b PF 6 are given in Table (see also Table S1 in the Supporting Information for selected bond lengths and angles). All of the cations 2a , b , 3b , 4a , b , and 5a – c are formed by three cyclic ligands, between which two metal atoms are located.…”
Section: Resultsmentioning
confidence: 99%
“…Herein we describe a straightforward approach to the 30-VE cationic complexes [CpCo(μ-1,3-C 3 B 2 Me 5 )M(ring)] + , on the basis of the reactions of anion 1 (as a thallium derivative) with [M(ring)X 2 ] 2 . The electrochemical behavior and structural features of the complexes synthesized are also described.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the reactions of compounds 1 and 2 with AgBF 4 in nitromethane followed by the addition of benzene yields the 30 electron triple decker complexes [CpCo(1,3 C 3 B 2 Me 5 )M(C 6 H 6 )] 2+ (3,4) in 80-85% yields (Scheme 1). * It is assumed that the reaction pro ceeds through the intermediate formation of labile solvate complexes [CpCo(μ 1,3 C 3 B 2 Me 5 )M(MeNO 2 ) 3 ] 2+ .…”
Section: Resultsmentioning
confidence: 99%